Resuscitation Patterns and Massive Transfusion for the Critical Bleeding Dog—A Multicentric Retrospective Study of 69 Cases (2007–2013) - Tucker, Claire; Winner, Anna; Reeves, Ryan; Cooper, Edward S.; Hall, Kelly; Schildt, Julie; Brown, David; Guillaumin, Julien (Frontiers in Veterinary Science, 2022)
ABSTRACT PAGE Objective – To describe resuscitation patterns of critically bleeding dogs, including those receiving massive transfusion (MT). Design –Retrospective study from 3 universities (2007-2013). Animals – Critically bleeding dogs, defined as dogs who received ≥ 25 mL/kg of blood products for treatment of hemorrhagic shock caused by blood loss. Measurements and Main Results – Sixty-nine dogs met the inclusion criteria. Sources of critical bleeding were trauma (26.1%), intra/perioperative surgical period (26.1%), miscellaneous (24.6%), and spontaneous hemoabdomen (23.1%). Median (range) age was 7 years (0.5-18). Median body weight was 20 kg (2.6-57). Median pre-transfusion hematocrit, total protein, systolic blood pressure and lactate were 25% (10-63), 4.1 g/dL (2-7.1), and 80 mm Hg (20-181) and 6.4 mmol/L (1.1-18.2), respectively. Median blood product volume administered was 44 mL/kg (25-137.4). Median plasma to red blood cell ratio was 0.8 (0-4) and median non-blood product resuscitation fluid to blood product ratio was 0.5 (0-3.6). Massive Transfusion (MT) was given to 47.8% of dogs. Survival rate was 40.6%. The estimated odds of survival were higher by a factor of 1.8 (95% CI: 1.174, 3.094) for a dog with 1 g/dL higher total protein above reference interval and were lower by a factor of 0.6 (95% CI: 0.340, 0.915) per 100% prolongation of partial thromboplastin time above the reference interval. No predictors of MT were identified. Conclusions: Critical bleeding in dogs was associated with a wide range of resuscitation patterns and carries a guarded to poor prognosis.